HIGH TECH APPROACHES TO FORECASTING THE LINEARLY EXTENDED OBJECTS - Spiridonov, E. S.; Yemielianov, R. Ye.; Kulikova, I. V.; Dienisov, O. O.; Zheriebtsova, V. (Science and Transport Progress, 2003)
The high technology approaches to forecasting development of uniform transport system are considered in the article.